2020
DOI: 10.1002/jhet.3910
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and antimicrobial studies of N‐substituted‐pyrazoline‐based new bisheterocycles

Abstract: In the present study, the four series of N‐acetyl/N‐carbothioamide/N‐carboxamide/N‐phenyl‐based new bispyrazolines have been synthesized. These symmetrical bisheterocyclic products were prepared efficiently from the ring‐closure reactions of new bischalcones 2a‐d with appropriate cyclizing agents (hydrazine hydrate, thiosemicarbazide, semicarbazide, and phenyl hydrazine) under the alkaline ethanolic conditions. The compounds 2a‐d were obtained by treating hydroxyl‐substituted chalcone 1 with various dihalogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Shehneela Nisa and Mohamad Yusuf effectively produced the symmetrical bispyrazoline products 87 a – t (Figure 14) from the ring‐closure processes [136] . The study found that N‐acetyl 87 e – h and N‐carbothioamide 87 i – l ‐substituted bispyrazolines have potential antibacterial properties compared to other symmetrical bis heterocyclic compounds.…”
Section: Pharmacological Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…Shehneela Nisa and Mohamad Yusuf effectively produced the symmetrical bispyrazoline products 87 a – t (Figure 14) from the ring‐closure processes [136] . The study found that N‐acetyl 87 e – h and N‐carbothioamide 87 i – l ‐substituted bispyrazolines have potential antibacterial properties compared to other symmetrical bis heterocyclic compounds.…”
Section: Pharmacological Activitymentioning
confidence: 91%
“…Shehneela Nisa and Mohamad Yusuf effectively produced the symmetrical bispyrazoline products 87 a-t (Figure 14) from the ring-closure processes. [136] The study found that N-acetyl 87 e-h and N-carbothioamide 87 i-l-substituted bispyrazolines have potential antibacterial properties compared to other symmetrical bis heterocyclic compounds. The antimicrobial analyses revealed that most intermediate analogs 87 a-d had moderate effects against the tested bacteria, with a MIC of 16 μg/mL.…”
Section: Antibacterialsmentioning
confidence: 97%
“…Because of their several biological activities, pyrazolines have attracted increasing interest in the field of medicinal chemistry. Their antioxidant, 11 anti-inflammatory, 12 antimicrobial, 13,14 antituberculosis, 13 antibacterial 15,16 and antitumoral [17][18][19][20] properties are due to the presence of a heterocyclic ring and their structural variety. 19,21 Pyrazolines are five-membered heterocyclic compounds containing two nitrogen atoms.…”
Section: Introductionmentioning
confidence: 99%